Taxonomic remarks on selected Asian Lepidium (Brassicaceae) - German, Dmitry (Phytotaxa, 2020)
Taxonomy of some predominantly SW to Central Asian and, to a lesser degree, SE European members of Lepidium is updated. Lepidium crassifolium Pall. (non Waldst. & Kit.) is typified and synonymized with L. cartilagineum subsp. cartilagineum. Lepidium crassifolium var. ramosissimum is assigned to synonymy of L. cartilagineum subsp. crenatifolium. The neglected Lepidium descemetii is found to be a prior name for L. pumilum and L. tuzgoeluense and the need of limitation of its priority in favour of L. pumilum is highlighted. Occurrence of the species in Iran is not confirmed as well as the wide distribution of L. caespitosum in Turkey that is restricted to north-eastern Anatolia. Finally, Lepidium pabotii is found conspecific with L. fenestratum, comb. nov. and L. gobicum is relegated to synonymy of L. apetalum.